ANALISIS NILAI EKONOMI LIMBAH INDUSTRI KELAPA SAWIT DI PT. SANDABI INDAH LESTARI KABUPATEN BENGKULU UTARA) - Afiffah, Shofaul; Sriyoto, Sriyoto; Sumantri, Bambang (Jurnal AGRISEP, 2016)
Solid and liquid waste from PT. Sandabi Indah Lestari only do the management and utilization. The Company not count the economic value of waste produced. If the company counting and know about the economic value of waste, so the company will know advantage which ought to be accepted by PT. SIL. This research aim to identify kind and form of waste, and also counting and analysis economic value of waste yielded by PT. SIL. Analysis method the use is descriptive analysis for first aim and quantitative descriptive for second aim. Based on the research result, solid waste the yielded is empty fruits bunch, fiber, shell and solid. Liquid waste consist of condensate and sludge oil. The form and benefit from each yielded waste different each other. Total economic value of waste yielded by PT. SIL is Rp 518.140.954,47/month. The mentioned mean that the waste of yielded by PT. SIL have economic value and than the company getting of benefit, that is the company getting income from waste is Rp 518.140.954,47/month.